MODELING OF LOADING AND ANALYSIS OF THE STRESS-STRAIN STATE OF PORTAL CRANE GANTRY ELEMENT - Sahirov, Y. H.; Suglobov, V. V. (Science and Transport Progress, 2019)
Purpose. The main purpose of this work is to simulate the gantry loading during operation of the Azovets portal crane, the analysis of the actual stress-strain state of the gantry metal structure elements. The object of the study is the pattern of stress distribution in the gantry elements. Methodology. To achieve this purpose the following methods were used: analytical engineering calculations, simulation modeling, finite elements, and visual-optical method for examining the state of the crane metal structure. Findings. The loaded state of the metal structure of the portal crane was modeled with the use of the CAD/CAE system and its strength was calculated by the finite element me-thod. The results of calculations and analysis of the stress-strain state are given. The obtained regularity of stress distribution in the pillar elements clearly showed that the stresses are unevenly distributed. The stress-strain state of the portal elements is rather complicated, uneven and requires modernization. Originality. The existing methods for the metal structures design of portal cranes were further developed. For the first time, a methodology of designing rational metal structures according to the criteria of uniform stress distribution and smoothness of the power flow was proposed. For the first time, the criteria for assessing the uniformity of stress distribution and smoothness of power flow scientifically substantiated. For the first time, solid-state models of the portal crane metal structure were developed, which allow determining the pattern of stress/load distribution and smoothness of the power flow in them. Practical value. A spatial solid-state computer model of the Azovets portal crane and a methodology for strength analysis and rational design of the metal structure for portal cranes were developed and implemented. The recommendations for repair and strengthening of the gantry components of the Azovets portal crane were scientifically grounded. The results of theoretical and practical research are used in the State Higher Educational Institution «PSTU» in teaching the courses «Designing Metal Structures LTM», «Basics of Computer Aided Design of Machines», «Automated Designing LTM», «Repair, Installation and Lubricants LTM»